Conception of Next Generation Networks - Šarić, Slavko; Balić, Jozo; Vidović, Rudo (Promet - Traffic&Transportation, 2004)
This article presents a review of the existing networks andthe NGN concept. By analysing the condition of the existingtelecommunication networks and services it is obvious that theyare different single-se1vice networks that cannot meet the requirementsof the users for various se1vices. The increased demandsof the users for telecommunication se1vices have inducedthe introduction of liberalization in the telecommunicationmarket. That opened the door for competition and greatinvestments in the development of telecommunication networks.The existing telecommunication networks orientated to thetransmission of voice and the existing data network could notbe adapted to new requirements without difficulties. That is thereason why the search for a solution for convergence and unionof a great number of different single-service networks started.The basic requirement was reduced in the end to the conceptionof the universal wideband data network that can meet all thedemands of the users by dividing the resources. As a collSequenceof that it was necessmy to find the solution for the transmissionof voice by a data network. The solution was seen in theerection of softswitch architecture for VoiP. Thus, the voicewould be transmitted by packets as one of the components indata transmission. It was necessary to define protocols for enablingthe operation in the NGN conception, as well as to thoroughlyobserve the problems of the JP telephony operation in regardto the real-time voice component. Apart from these tasks itwas necessmy to see how to adapt the existing networks into theNGN conception and to provide interaction between differentnetworks and different layers of networks by applying certainstandards and protocols. The awareness of the necessity ofgradual introduction and realization of NGN conception hasbecome obvious, always in the relation to the existing conditionof PSTN and the users’ demands. Special attention should begiven to the introduction of IN as a tool for the realization ofadditional se1vices and for enabling the control in NGN. Theproblem of JP routers for NGN has also been mentioned, aswell as the importance of the new core generation of optical networks.The conceptual framework of NGN is based today onIP/ATM transport technology, which is at this level of developmentgenerally accepted as the optimal transp011 solution. The problem of addressing caused by the insufficient address spaceof Ipv4 has been stressed and the solution of that problem hasbeen anticipated with the introduction of lpv6 technology,which, due to its complexity and high costs, would be graduallyintroduced by a dual approach into the system.The differentiating elements of NGN in relation to the existingnetworks have been specially pointed out. The modulm;that is, plane nature of the NGN conception in relation to thevertical and hierarchical conception of PSTN has beenstressed, as well as the pdvileges that this open conception offerswhen choosing the equipment of the highest quality by differentmanufacturers. Both existing, voice (TDM) and data(NGN) (ATM/IP), networks will act parallel in the next yearsuntil new solutions to NGN will have been introduced.